HUBUNGAN KECERDASAN EMOSIONAL DENGAN SIKAP PERCAYA DIRI PADA SISWA KELAS III SD MUSLIM SUKSA SATUN-THAILAND - Aji Joko Sutrisno; Chairunnisa Amelia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the relationship between emotional intelligence and self-confidence among third-grade students at SD Muslim Suksa Satun–Thailand. The research design employed a quantitative correlational method with a sample of 25 students selected through total sampling. Data collection instruments consisted of two standardized questionnaires that had been tested for validity and reliability. Product Moment analysis results showed a positive but insignificant relationship between emotional intelligence and self-confidence (r = 0.268; p = 0.195). These findings indicate that other factors may contribute to the development of students’ self-confidence. The practical implication of this study highlights the importance of a holistic approach that does not focus solely on emotional intelligence.